Activating and sustaining c-Myc by depletion of miR-144/451 gene locus contributes to B-lymphomagenesis. Issue 10 (8th March 2018) - Ding, Lan; Zhang, Yanqing; Han, Lingling; Fu, Lei; Mei, Xia; Wang, Jijun; Itkow, Jacobi; Elabid, Afaf; Pang, Lei; Yu, Duonan
Abstract Hyper activity of protooncogenec-Myc is one of the hallmarks of highly aggressive lymphomas. However, the mechanism of howc-Myc is subjected to activation and amplification is still not well defined. In this study, we use gene knockout strategy to show that targeted depletion of a well-conserved microRNA gene locusmiR-144/451 initiates tumorigenesis including B-lymphoma development in aged mice. This is due, at least in part, to the direct activation of thec-Myc gene by loss ofmiR-144/451 expression in hematopoietic cells. Moreover, oncoprotein c-Myc inversely regulatesmiR-144/451 expression by directly binding to themiR-144/451 promoter region, forming a miRNA-Myc positive feedback loop to safeguard the high level of c-Myc in B-lymphocytes. We also demonstrate that this miRNA-Myc crosstalk is disrupted in human diffuse large B-cell lymphomas with aberrantc-Myc expression. Therefore, our findings provide strong evidence, for the first time, that deficiency ofmiR-144/451 expression may play a bona fide role in derepression of silenced c-Myc, which contributes to tumor development including B-lymphomagenesis.